2008
DOI: 10.1136/ard.2008.089441
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of a screening questionnaire for psoriatic arthritis: the Toronto Psoriatic Arthritis Screen (ToPAS)

Abstract: Our simplified index is very good at classifying those who are not diagnosed with PsA and those who are diagnosed with PsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
143
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(146 citation statements)
references
References 11 publications
0
143
1
2
Order By: Relevance
“…Simple and validated screening tests, such as the Psoriatic Arthritis Screening and Evaluation (PASE) tool, the Psoriasis Epidemiology Screening Tool (PEST), the Toronto Psoriatic Arthritis Screen (ToPAS) and the Early ARthritis for Psoriatic patients (EARP) questionnaire, have been assessed to determine whether people with suspected PsA should be referred to confirm the diagnosis (Table 1). 16, 17, 18, 19 Despite such tools, the paucity of data from secondary care regarding their feasibility, sensitivity and specificity, along with the lack of consensus on which tool is best, hampers their widespread clinical use. In some cases the sensitivities and specificities of the tools have been found to be lower than originally reported; when the PASE, PEST and ToPAS questionnaires were compared in the CONTEST study, it was found that they would identify cases of musculoskeletal disease other than PsA, and there was little difference between the performance of the tools 20…”
Section: Overcoming Barriers To the Early And Accurate Diagnosis Of Psamentioning
confidence: 99%
“…Simple and validated screening tests, such as the Psoriatic Arthritis Screening and Evaluation (PASE) tool, the Psoriasis Epidemiology Screening Tool (PEST), the Toronto Psoriatic Arthritis Screen (ToPAS) and the Early ARthritis for Psoriatic patients (EARP) questionnaire, have been assessed to determine whether people with suspected PsA should be referred to confirm the diagnosis (Table 1). 16, 17, 18, 19 Despite such tools, the paucity of data from secondary care regarding their feasibility, sensitivity and specificity, along with the lack of consensus on which tool is best, hampers their widespread clinical use. In some cases the sensitivities and specificities of the tools have been found to be lower than originally reported; when the PASE, PEST and ToPAS questionnaires were compared in the CONTEST study, it was found that they would identify cases of musculoskeletal disease other than PsA, and there was little difference between the performance of the tools 20…”
Section: Overcoming Barriers To the Early And Accurate Diagnosis Of Psamentioning
confidence: 99%
“…3 Moll and Wright concluded from a review of epidemiological studies and scientifically support the concept that psoriatic arthritis is a single entity, with clinical, serological and radiological characteristics, and provided the earliest diagnostic criteria for psoriatic arthritis. [4][5][6] Nowadays it is generally agreed that while psoriatic arthritis can be classified among spondyloarthropathies, a family of disorders sharing common features like inflammatory arthritis, axial involvement, enthesopathy, absence of rheumatoid factor and association with HLA. 5,6 There is no general agreement in the literature regarding the prevalence of psoriatic arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Nowadays it is generally agreed that while psoriatic arthritis can be classified among spondyloarthropathies, a family of disorders sharing common features like inflammatory arthritis, axial involvement, enthesopathy, absence of rheumatoid factor and association with HLA. 5,6 There is no general agreement in the literature regarding the prevalence of psoriatic arthritis. The estimate of prevalence has been difficult because of the paucity of widely accepted classification or diagnostic criteria and the difficulty of most experts in making a correct diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…While this approach does not replace the need rheumatologist, help in identifying subjects for epidemiological studies and perhaps in identifying individuals who should be referred for rheumatology consultation [15,16].…”
Section: Discussionmentioning
confidence: 99%